2016 update of the ASAS-EULAR management recommendations for axial spondyloarthritis. Issue 6 (13th January 2017) - van der Heijde, Désirée; Ramiro, Sofia; Landewé, Robert; Baraliakos, Xenofon; Van den Bosch, Filip; Sepriano, Alexandre; Regel, Andrea; Ciurea, Adrian; Dagfinrud, Hanne; Dougados, Maxime; van Gaalen, Floris; Géher, Pál; et al.
Abstract : To update and integrate the recommendations for ankylosing spondylitis and the recommendations for the use of tumour necrosis factor inhibitors (TNFi) in axial spondyloarthritis (axSpA) into one set applicable to the full spectrum of patients with axSpA. Following the latest version of the European League Against Rheumatism (EULAR) Standardised Operating Procedures, two systematic literature reviews first collected the evidence regarding all treatment options (pharmacological and non-pharmacological) that were published since 2009. After a discussion of the results in the steering group and presentation to the task force, overarching principles and recommendations were formulated, and consensus was obtained by informal voting. A total of 5 overarching principles and 13 recommendations were agreed on. The first three recommendations deal with personalised medicine including treatment target and monitoring. Recommendation 4 covers non-pharmacological management. Recommendation 5 describes the central role of non-steroidal anti-inflammatory drugs (NSAIDs) as first-choice drug treatment. Recommendations 6–8 define the rather modest role of analgesics, and disprove glucocorticoids and conventional synthetic disease-modifying antirheumatic drugs (DMARDs) for axSpA patents with predominant axial involvement. Recommendation 9 refers to biological DMARDs (bDMARDs) including TNFi and IL-17 inhibitors (IL-17i) for patients with high disease activity despite the use (or intolerance/contraindication) of at least two NSAIDs. In addition, they should either have an elevated C reactive protein and/or definite inflammation on MRI and/or radiographic evidence of sacroiliitis. Current practice is to start with a TNFi. Switching to another TNFi or an IL-17i is recommended in case TNFi fails (recommendation 10). Tapering, but not stopping a bDMARD, can be considered in patients in sustained remission (recommendation 11). The final two recommendations (12, 13) deal with surgery and spinal fractures. The 2016 Assessment of SpondyloArthritis international Society-EULAR recommendations provide up-to-date guidance on the management of patients with axSpA.